2008
DOI: 10.4314/thrb.v10i1.14335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glucose-6-phosphate dehydrogenase deficiency and haemoglobin S in high and moderate malaria transmission areas of Muheza, north-eastern Tanzania

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency and haemoglobin S (HbS) are very common genetic disorders in sub Saharan Africa, where malaria is endemic. These genetic disorders have been associated with protection against malaria and are therefore under strong selection pressure by the disease. In November-December 2003, we conducted a cross-sectional survey to determine the prevalence of G6PD deficiency and HbS in the population and relate these to malaria infection and haemoglobin levels in lowland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, nine studies whose data either cannot be extracted, overlapped, or combined with the rest of the data, and thus were excluded. Among the 30 included studies, the species of Plasmodium are only Plasmodium falciparum in 17 studies3571011181920212223242526272829, only Plasmodium vivax in one study30, and combined species ( P. falciparum with P. vivax, P. falciparum with P. malariae, P. vivax with P. malariae , and P. falciparum with P. vivax and P. malariae ) in eight studies1415313233343536. Jalloh 200432, Tantular 199936, and Kruatrachue 196215 reported separate data for P. vivax which meta-analyzed with that of Leslie 201030.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nine studies whose data either cannot be extracted, overlapped, or combined with the rest of the data, and thus were excluded. Among the 30 included studies, the species of Plasmodium are only Plasmodium falciparum in 17 studies3571011181920212223242526272829, only Plasmodium vivax in one study30, and combined species ( P. falciparum with P. vivax, P. falciparum with P. malariae, P. vivax with P. malariae , and P. falciparum with P. vivax and P. malariae ) in eight studies1415313233343536. Jalloh 200432, Tantular 199936, and Kruatrachue 196215 reported separate data for P. vivax which meta-analyzed with that of Leslie 201030.…”
Section: Resultsmentioning
confidence: 99%
“…The odds ratios (OR) from 19 datasets obtained from 14 studies3571014151820222429313236 were pooled for this meta-analysis. There was significant heterogeneity among the studies; thus, random effect model was applied for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to wide regional differences, the frequencies of individual risk alleles can differ markedly between geographically contiguous but reproductively isolated groups. A dramatic example is G6PD deficiency in Tanzania, where prevalence in lowland and highland populations (11.3% and 4.4%, respectively) mirrors that of malaria [7]. Thus, genetic testing priorities should include pretest probabilities in subpopulations rather than geographic averages, an onerous requirement for genetics programs in LMICs.…”
Section: The Global Challenge Of Genetic Diseasesmentioning
confidence: 99%
“…For alpha thalassaemia, studies suggested both protection against and enhancement of malaria [5,6,27,28]. For G6PD deficiency, studies in Africa [29][30][31][32], but not Asia [8,[33][34][35] suggested protection against uncomplicated malaria. Some discrepancies in findings might be attributed to differences between studies in human populations, transmission settings, and study designs.…”
Section: Introductionmentioning
confidence: 99%